Plantar fasciitis and pain symptom are related to the longitudinal arch shape and not to the plantar pressure during running - Sacco, I. C. N.; Ribeiro, A. P.; Trombini-Souza, F.; Tessutti, V.; João, S. M. A. (ESM 2010 emed scientific meeting, 2010)
Plantar fasciitis has been the third most common disease in runners, but its pathogenesis is still inconclusive. Changes in the longitudinal plantar arch and mechanical overload on the feet, have been described as risk factors for developing plantar fasciitis. However, there are few studies investigating these factors during running in individuals with and without plantar fasciitis. Most of the literature investigated biomechanical parameters of the plantar fasciitis during gait and the results are still controversial, mainly because it is unclear the effect of pain associated with the disease over those parameters. Wearing et al. (2007) discussed that symptomatic individuals make some adaptations during gait to reduce forces over the rearfoot and, consequently, increase loads over adjacent foot areas, such as over the mid and forefoot, as also observed by some authors. According to biomechanical studies, it is possible that the plantar pressure distribution in individuals with plantar fasciitis would be different during the symptomatic and asymptomatic phases of the disease, and the pattern could be even more different during running. The purpose of this study was to investigate the association between plantar fasciitis and its pain symptom with the longitudinal plantar arch (LPA) shape and plantar pressure distribution during running.